PENGEJARAN KEPENTINGAN NASIONAL DI BIDANG ENERGI OLEH PEMERINTAH TURKI MELALUI KERJASAMA DENGAN IRAN TAHUN 2002-2009 - Kurnianta, Mira Nanda; Fasisaka, Idin; Nugraha, A. A. B. Surya Widya (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2017)
ABSTRACT Energy is a main requirement in a country. Increased energy consumption continues to occur in economic based industrial country, one of them is Turkey. Increase in energy consumption gives impact to the energy supply problems. To handle the disruption in energy supply, Turkey pursues the energy interest through joint cooperation with Iran. This research aimed to describe the pursuit carried out by Turkey to handle domestic energy problems by cooperation with Iran. This research uses the concepts of economic well-being on energy, energy security, and strategic depth. Key Words: Turkey, Iran, Energy Security, Strategic Depth.